Overview of Antagonists Used for Determining the Mechanisms of Action Employed by Potential Vasodilators with Their Suggested Signaling Pathways - Yean, Chun Loh; Chu, Shan Tan; Yung, Sing Ch’ng; Ahmad, Mariam; Asmawi, Mohd Zaini; Mun, Fei Yam (MDPI, 2016)
This paper is a review on the types of antagonists and the signaling mechanism pathways that have been used to determine the mechanisms of action employed for vasodilation by test compounds. Thus, we exhaustively reviewed and analyzed reports related to this topic published in PubMed between the years of 2010 till 2015. The aim of this paperis to suggest the most appropriate type of antagonists that correspond to receptors that would be involved during the mechanistic studies, as well as the latest signaling pathways trends that are being studied in order to determine the route(s) that atest compound employs for inducing vasodilation. The methods to perform the mechanism studies were included. Fundamentally, the affinity, specificity and selectivity of the antagonists to their receptors or enzymes were clearly elaborated as well as the solubility and reversibility. All the signaling pathways on the mechanisms of action involved in the vascular tone regulation have been well described in previous review articles. However, the most appropriate antagonists that should be utilized have never been suggested and elaborated before, hence the reason for this review.